A Rare Presentation of Tubercular Meningitis as Persistent Neutrophilic Meningitis - Ralot, Tarun (Malays J Med Sci, 2017)
Persistent neutrophilic meningitis is an atypical form of chronic meningitis defined as clinical meningitis with a cerebrospinal fluid (CSF) analysis suggestive of neutrophilic pleocytosis that persists for more than one week despite giving empirical antimicrobial therapy. The predominant presentation of tubercular meningitis is with CSF lymphocytic pleocytosis and even if early phase of the disease presents with neutrophilic pleocytosis, no persistence is usually observed for more than one week. We hereby report the case of an immunocompetent man aged 25 years with tubercular meningitis manifesting as persistent neutrophilic meningitis which is very rare as an entity in tubercular meningitis (TBM). Patient was started on anti-tubercular therapy based on the granulomas in magnetic resonance imaging (MRI) of the brain after which there was a reduction in total cell count in CSF but persisting neutrophilic predominance. Patient improved clinically and was given a full course of anti-tubercular treatment (ATT) thereafter.